How a Private Educational Institution in South Brazil Managed to Create a University Innovation and Entrepreneurship Ecosystem - Kaniak, Vivien Mariane Massaneiro; Teixeira, Rivanda Meira; Carvalho, Ana Carolina Vilela; Segatto, Andréa Paula (Revista de Negócios, 2023)
This article aims to describe the dynamic of a university innovation and entrepreneurship ecosystem, as well as the actions developed by a private university in southern Brazil to create it. Through a descriptive qualitative approach, the research strategy consisted of a case study in which data were obtained through six interviews, non-participant observation, and documentary analysis. The results demonstrated that the university managed to reach an innovation and entrepreneurship ecosystem once they reinforced favorable institutional conditions for entrepreneurship and developed a structured department of entrepreneurship education that gives support to future entrepreneurs. Once the theme has not yet been widely explored in the literature, this article aims to contribute both to broaden the debate and to present a case of a South American private university that may serve as a model for other educational institutions that wish to create or reinforce their university innovation and entrepreneurship ecosystems.